Volume 1: Fuels and Combustion, Material Handling, Emissions; Steam Generators; Heat Exchangers and Cooling Systems; Turbines, 2013
DOI: 10.1115/power2013-98088
|View full text |Cite
|
Sign up to set email alerts
|

Specified Maintenance of Steam Turbines in Geothermal Power Plants

Abstract: In a geothermal power plant the working fluid used to produce electricity is often wet steam composed of corrosives chemicals. In this situation, more frequent maintenance of the equipment is required. By constructing an overview for maintenance in geothermal power plants and how it can be done with minimum power outages and cost, the geothermal energy can be made more competitive in comparison to other energy resources. This work is constructed as a part of a project, which has the aim of mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Reliability evaluation is carried out using qualitative and quantitative analysis. Failure Mode and Effect Analysis (FMEA) is frequently used to describe the potential failures and the critical components of steam turbine using qualitative assessment [3] [4][5]. A study once examined the diaphragm was the top priority of steam turbine components that should be maintained refered to the highest risk priority number (RPN) [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliability evaluation is carried out using qualitative and quantitative analysis. Failure Mode and Effect Analysis (FMEA) is frequently used to describe the potential failures and the critical components of steam turbine using qualitative assessment [3] [4][5]. A study once examined the diaphragm was the top priority of steam turbine components that should be maintained refered to the highest risk priority number (RPN) [4].…”
Section: Related Workmentioning
confidence: 99%
“…RPN was calculated by multiplying the value of Severity (S), Occurrence (O), and Detection (D). In this study, the potential failures were adapted from previous researches [3][4] and combined with direct identification. FMEA questionnaires was spreaded to 5 respondents in the power plant.…”
Section: Reliability Evaluationmentioning
confidence: 99%
“…Sedangkan, Gambar 8(b) adalah siklus daya operasi sampai overhaul, di mana overhaul pada umumnya dilakukan 4 tahun sekali. Alasannya, keausan akibat erosi partikel padat yang melewati poros berpotensi menimbulkan kerusakan yang lebih besar pada poros, terutama bagian labyrinth seal setelah melewati jangka waktu tersebut [12]. Garis merah pada gambar grafik menandakan panjangnya 1 siklus pada Gambar 8(b).…”
Section: Kekuatan Lelah Dan Siklus Beban Porosunclassified
“…Almar Gunnarsson et al [ 15 ] reported the corrosion–erosion and wear effect on the turbine blades operating in a geothermal environment. Cost reduction in maintenance is required in order to increase the competitiveness of this type of resource in the renewable energy market.…”
Section: Introductionmentioning
confidence: 99%